2022
DOI: 10.1088/1361-6579/ac8bc2
|View full text |Cite
|
Sign up to set email alerts
|

The calculation of electrical impedance tomography based silent spaces requires individual thorax and lung contours

Abstract: Objective: The present study evaluates the influence of different thorax contours (generic vs individual) on the parameter “silent spaces” computed from electrical impedance tomography (EIT) measurements. Approach: Six patients with acute respiratory distress syndrome were analyzed retrospectively. EIT measurements were performed and the silent spaces were calculated based on (1) patient-specific contours Sind, (2) generic adult male contours SEidorsA and (3) generic neonate contours SEidorsN. Main results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This method requires the definition of lung regions in the EIT images, which is a difficult issue in EIT and critical for the correct interpretation. Individualized regions are needed [8] which has not been done so far. A new method has recently been proposed that might improve the identification of lung regions-of-interest [9 ▪ ].…”
Section: How Can Electrical Impedance Tomography Help In Setting Posi...mentioning
confidence: 99%
“…This method requires the definition of lung regions in the EIT images, which is a difficult issue in EIT and critical for the correct interpretation. Individualized regions are needed [8] which has not been done so far. A new method has recently been proposed that might improve the identification of lung regions-of-interest [9 ▪ ].…”
Section: How Can Electrical Impedance Tomography Help In Setting Posi...mentioning
confidence: 99%
“…Medical images of patients (such as CT images) can provide additional spatial information on patient geometry for the external boundary and location of organs. Recent work has shown that using a custom mesh can improve EIT estimates of lung inhomogeneity (Yang et al, 2021) in ARDS patients, but generating custom meshes manually is not always feasible, and automatic segmentation of CT images is not always reliable. This chapter uses diagnostic CT images from 4 subjects to design and test a tool to create custom meshes for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Higher spatial accuracy in identified organs and regions of interest could allow for easier isolation of the perfusion signal, and more accurate measures of perfusion and ventilation with EIT. Motivated by the work presented by Yang et al (2021), the work in this chapter focuses using custom meshes to improve measures of ventilation in the lungs. We hypothesize this might be able to better guide ventilation and improve treatment outcomes for patients with acute respiratory distress syndrome (ARDS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations